ChemInform Abstract: 3‐Chloro‐1‐lithiopropene, a Functional Organolithium Reagent, and Its Reactions with Alkylboronates to Give 3‐Alkylprop‐1‐en‐3‐ols. Issue 10 (11th March 2014) - Smith, Keith; Elliott, Mark C.; Jones, D. Heulyn
Abstract Treating 1‐bromo‐3‐chloropropene (II) with tBuLi leads to the formation of unstable 3‐chloro‐1‐lithiopropene which is trapped in situ by alkylboronic esters.